A Retrospective Longitudinal Study on Venous Thromboembolisms: The Impact of Active Monitoring on the Venous Thromboembolism Management Practices of Healthcare Providers to Improve Patient Outcomes - Rateb Abd Alrazak Daowd; Ateeq Mohamad Algarni; Majed Abdulhadi Almograbi; Sara Majed Saab; Naif Mansour Alrashed; Maryam Mohammad Harthi; Amira Fatmah Paguyo Quilapio; Ibrahim Numan Alnajjar; Shahzad Ahmad Mumtaz; Raed Fahad Albusayyis; Dalya Ali Aljumaiah; Yazeed Alsalamah; et al. (Journal of Mind and Medical Sciences)
Venous thromboembolism (VTE) is a relatively common condition that is the leading cause of preventable deaths in developed nations. VTE encompasses deep vein thrombosis (DVT) and pulmonary embolism (PE) and affects both hospitalized and non-hospitalized patients. When left untreated, VTE is associated with substantial morbidity and mortality; accurate risk assessment and appropriate prophylaxis programs are therefore vital, as overlooked risk factors of these processes can potentially result in misdiagnosis and inappropriate treatment of the condition, with associated complications. In this study, we aimed to assess the impact of active monitoring on VTE management practices among healthcare providers to improve patient outcomes at Imam Abdulrahman Al Faisal Hospital (IAFH) in Riyadh, Saudi Arabia, from April 2018 to July 2023. In this study, a longitudinal retrospective study design was utilized and data from 33,237 admitted patients were analyzed using a Statistical Process Control (SPC) chart to evaluate the relationship between VTE risk assessment, active monitoring, and patient outcomes. In total, 11 cases of hospital-acquired VTE were identified, with patients aged 18–40 years representing most cases (7 out of 11 cases) and a male predominance of 54.5%. The overall VTE incidence rate during the study period was 0.31%, or one case per 11,000 admissions, including four cases of PE and seven cases of DVT. The results of this study indicate that active monitoring through continuous education and regular patient rounds significantly improves adherence to VTE risk assessment and prophylaxis at IAFH. The researchers attributed the increased identification and timely reporting of VTE cases to vigilance by healthcare providers and not to a decline in the quality of care. A comprehensive multidisciplinary strategy for VTE management and continuous quality improvement can aid in reducing VTE-related morbidity and improve patient outcomes. Lastly, we recommend addressing the risk factors associated with the occurrence of hospital-acquired VTE and performing post-discharge follow-ups of patients.